N-glycosylation of UNC93B1 at a Specific Asparagine Residue Is Required for TLR9 Signaling - Song, Hyun-Sup; Park, Soeun; Huh, Ji-Won; Lee, Yu-Ran; Jung, Da-Jung; Yang, Chorong; Kim, So Hyun; Kim, Ho Min; Kim, You-Me (Frontiers in Immunology, 2022)
Toll-like receptors (TLRs) play critical roles in the first line of host defense against pathogens through recognition of pathogen-associated molecular patterns and initiation of the innate immune responses. The proper localization of TLRs in specific subcellular compartments is crucial for their ligand recognition and downstream signaling to ensure appropriate responses against pathogens while avoiding erroneous or excessive activation. Several TLRs, including TLR7 and TLR9 but not TLR4, depend on UNC93B1 for their proper intracellular localization and signaling. Accumulating evidences suggest that UNC93B1 differentially regulates its various client TLRs, but the specific mechanisms by which UNC93B1 controls individual TLRs are not well understood. Protein N-glycosylation is one of the most frequent and important post-translational modification that occurs in membrane-localized or secreted proteins. UNC93B1 was previously shown to be glycosylated at Asn251 and Asn272 residues. In this study, we investigated whether N-glycosylation of UNC93B1 affects its function by comparing wild type and glycosylation-defective mutant UNC93B1 proteins. We first found that glycosylation of Asn251 and Asn272 residues can occur independently of each other and mutation of neither N251Q or N272Q in UNC93B1 altered expression and localization of UNC93B1 and TLR9. In contrast, CpG DNA-stimulated TLR9 signaling was severely inhibited in cells expressing UNC93B1(N272Q), but not in cells with UNC93B1(N251Q). We further found that glycosylation at Asn272 of UNC93B1 is essential for the recruitment of MyD88 to TLR9 and the subsequent downstream signaling. On the other hand, the defective glycosylation at Asn272 did not affect TLR7 signaling. Collectively, these data demonstrate that the glycosylation at a specific asparagine residue of UNC93B1 is required for TLR9 signaling and the glycosylation status of UNC93B1 differently affects activation of TLR7 and TLR9.